PENGARUH KOMUNIKASI GURU TERHADAP PERILAKU BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI IPS SMK MADANI MAKASSAR - Sumarni; Erni Rismawanti; Israwati Akib (CV. ADIBA AISHA AMIRA, 2024)
This research aims to determine teacher communication and learning behavior for class XI IPS SMK Madani Makassar. The sample was determined using saturated sampling, where the entire population of 30 people was sampled. The data collection technique used is questionnaire collection, direct observation of parties who are related to the problem being researched. Data analyzed using simple linear regression analysis techniques shows that student learning behavior communication can be formulated as follows. Partial test results show that teacher communication and student learning behavior have a positive and significant effect.